A historical sensibility Sir Michael Howard and the International Institute for Strategic Studies, 1958-2019 - Howard, Michael (Routledge, for the International Institute for Strategic Studies, 2020)
With the death of Professor Sir Michael Howard, The International Institute for Strategic Studies (IISS) lost not only its president emeritus but the last of its founders and intellectual parents. The foremost military historian of his generation, Sir Michael embodied and epitomised a historical sensibility that informed all his writing. He will forever remain an icon not only for historians, but for all those who acknowledge the indispensability of history and the historical sensibility for any true understanding of present events. In tribute to Sir Michael and in celebration of his life and work, this Adelphi book collects a selection of his remarks and writings for IISS publications over six decades, as well as previously unprinted material. Through this collection, these works will reach a new generation of readers and be made more accessible to those fortunate enough to have read them already. They illustrate Sir Michael's role in the Institute's creation and his abiding presence in its evolving intellectual life, and serve as a historical document, tracing the development of strategic thought and preoccupations from the 1950s to the recent past. In addition to their historical value, Sir Michael's conclusions retain their immediacy and power. This book is therefore of direct relevance to anyone interested in contemporary events: whether the professional analyst, the student of international relations or the general reader.